Students’ Science Process Skills Through Generative Learning Model In the Topic of Light - Haris Rosdianto (STKIP Singkawang, 2019)
Science process skills is important to developing the quality of students’ learning in science. This research aimed to determine the effect of generative learning xmodel on students' science process skills of the topic Light. This type of research was pre-exprimental with One Group Pretest-Posttest Design. The population of this research consisted of all students of class VIII in SMPN 5 Singkawang City. The research samples consisted of the students of class VIII E the total number of 20 students and the sampling technique used was simple random sampling. The research instrument used in this research was description test. Data were analyzed by using paired t-test. From the calculation results was obtained the value of -tobtained < -tcritical or -21.36 < -2.093, then Ho was rejected and Ha was accepted at the level of significance α = 0.05. So it can be concluded that there was an effect of generative learning model on students’ science process skills in the topic of Light.